18 Head-to-Body Delivery by 'Two-Step' Approach: Effect on Umbilical Artery Hematocrit and PH. (October 2012) - Zanardo, V; Simbi, A; Guerrini, P; Gattolin, I; Trevisanuto, D; Cengio, V Dal; Straface, G
Abstract : Background: The timing of umbilical cord clamping has a profound effect on the amount of blood that remains in the infant's circulation at birth. However, there is no evidence to support a relationship between cord clamping time and other active management techniques of labor. Objective: To examine the association between head-to-body delivery by 'two-step' approach, that include waiting for the next contraction to deliver the shoulders, and early cord clamping (< 1 min) and its effect on the amount of blood that remains in the infant's circulation at birth and cord artery blood gas parameters. Study Design: Prospective observational study on 50 consecutive at term, uncomplicated vaginal deliveries with singleton cephalic fetuses during January 2012 in Policlinico Abano Terme, Abano Terme, Italy. Cord arterial blood gas parameters and hematocrit (Htc) were compared to the reference values obtained in 50 healthy, control neonates, matched for gestational age, vaginally delivered by 'one-step' approach. Data analysis was performed with SPSS for Windows statistical package (version 13). Results: In our study population, head-to-body interval was timed and was always inferior to 3 minutes. The groups had similar demographic and biomedical characteristics at baseline. The mean cord artery hematocrit (Hct 50.2 vs. 44.9; p<0.001) levels were significantly higher in the head-to-body interval 'two-step' approach group, but there was no significant difference in the umbilical artery pH (7.30 vs. 7.29; p=0.45). Conclusion: Head-to-body delivery by 'two-step' approach increases the red cell mass in term infants and does not increase the risk of neonatal academia.